Implementation of viscoelastic Hopkinson bars - Curry, Richard (University of Cape Town, 2014)
Includes bibliographical references (p. 107-112). === The properties of soft, viscoelastic materials at high strain rates are important in furthering our understanding of their role during blast or impact events. Testing these soft or low impedance materials using metallic bars in a split Hopkinson pressure bar setup, poor signal to noise ratios and impedance mismatching occur. One solution is to use polymeric Hopkinson bars. In this dissertation, Polycarbonate, Polymethyl Methacrylate and Nylon are considered for use as Hopkinson bars. Conventional Hopkinson bar analysis cannot be used on the polymeric bars due to the viscoelastic nature of the bar material. As stress waves propagate along the length of the bars, viscoelastic effects result in dispersion and attenuation. The main topic of this dissertation is to account for this viscoelastic material effect.